1989
DOI: 10.1063/1.857511
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the turbulence structure of subsonic and supersonic boundary layers

Abstract: A comparison of the turbulence structure of subsonic and supersonic boundary layers reveals that, despite broad similarities, significant differences exist. The length scales derived from space-time correlations indicate that the spanwise scales are almost identical but that the streamwise scales in the supersonic flow are about half the size of those in subsonic flow. The large-scale structures in the subsonic boundary layer appear to move slightly slower, and lean more toward the wall than those observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
2
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 16 publications
7
39
2
1
Order By: Relevance
“…This may explain the relatively large discrepancies between the present Reynolds stress profiles and the other results near the edge of the boundary layer. Nevertheless, the present Reynolds normal stress profile shows a good agreement with the experimental results of Muck et al [23] and Smits et al [12] for 0.4<y/< 0.8, despite a significantly higher Reynolds number Re  in their flows. The LES result displays a relatively lower value than the experimental data for y/  >0.4, which may be due to the low-Reynolds-number effects.…”
Section: Turbulent Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…This may explain the relatively large discrepancies between the present Reynolds stress profiles and the other results near the edge of the boundary layer. Nevertheless, the present Reynolds normal stress profile shows a good agreement with the experimental results of Muck et al [23] and Smits et al [12] for 0.4<y/< 0.8, despite a significantly higher Reynolds number Re  in their flows. The LES result displays a relatively lower value than the experimental data for y/  >0.4, which may be due to the low-Reynolds-number effects.…”
Section: Turbulent Propertiessupporting
confidence: 92%
“…However, the log-law region extending farther in the wall-normal direction in the present study is probably due to the large velocity gradient in supersonic boundary layers. And the fact that the intermittency profile in a supersonic boundary layer is fuller than the corresponding subsonic profile may be another explanation, according to Smits et al [12].…”
Section: Turbulent Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…a contraction of equation (1.1) neglecting the pressure work terms), and has provided the rationale for using incompressible turbulence models for flows up to Mach 5. While scaling for compressibility has been found to correlate the mean velocity with the low-speed database across smooth boundary layers [Van Driest (1951)] more recent experiments suggest that for turbulent quantities the current database is insufficient [Fernholz et al ( 1981), Smits et al (1989), Spina et al (1994), Dussauge et al (1996) and Smits and Dussauge (1996)] even for smooth flat plate boundary layers and that Morkovin's hypothesis may be more restrictive than originally believed.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling for compressibility has been found to correlate the mean velocity with the low-speed database across smooth boundary layers [Van Driest (1951)]. More recently, detailed compilations and analyses of available high-speed turbulence smooth wall data [Fernholz et al (1981), Smits et al (1989), Spina et al (1994), Dussuage et al (1996) and Smits and Dussuage (1996)] have been performed. In summary, the studies indicated that the database was insufficient to confirm turbulent property scaling and the realm of applicability of Morkovin's hypothesis might be more restrictive than originally believed.…”
Section: Smooth Flat Plate Turbulent Boundary Layers With Low Turbulencementioning
confidence: 99%